Achieving Marketing Performance through Orientation Innovation and Entrepreneurial Orientation - Karnowati, Nandang Bekti; Sudarto, Sudarto; Suwandari, Lusi; Prakoso, Fajar Adi; Apriandi, Devy Widya (Jurnal Manajemen Bisnis, 2023)
Research aims: The purpose of this study is to examine the connection between innovation orientation (IO) and entrepreneurial orientation (EO) and its role in mediating marketing orientation (MO) to achieve marketing performance (MP), specifically focusing on MSMEs in the culinary sector in Banyumas, Purbalingga, Cilacap, and Kebumen (Barlingmascakeb).Design/Methodology/Approach: Data were collected from 100 food industry businesses in Barlingmascakeb. Structural equation modeling (SEM) was used utilizing Smart PLS to analyze data.Research findings: The results demonstrated that innovation orientation had a positive effect on entrepreneurial orientation and marketing performance. EO, which mediated the relationship between IO and MP, acted as a partial mediator. RBV is still a relevant theory for MSMEs, where organizational resources are assets that need to be managed and become superior to expand in a dynamic market. The research findings also support the MBV theory, where the market is a necessary factor to be considered by MSMEs in business and entrepreneurial decision-making. RBV and MBV actually complement each other and have an important role in influencing marketing performance.Theoretical contribution/Originality: This study contributes to the management study literature, which has built an empirical model that encourages MSME marketing performance by investigating the relationship between IO, EO, and MO to support MSME marketing performance.Practitioners/Policy Implications: This study provides insight into culinary MSME entrepreneurs to focus on innovation orientation and not ignore market orientation as a supporter of innovation and marketing performance.Research Limitations/Implications: This research only focused on MSMEs in the culinary sector, so generalizations and findings were limited. Therefore, future studies are expected to combine larger and more diverse samples.